Periplasmic protein changes in response to over-expression of recombinant protein in escherichia coli - Heidary, Somayyeh (2013)
Because of its many beneficial features, Escherichia coli is widely used as host for recombinant protein production. However, one major disadvantage of using E. coli is the formation of inclusion body especially when the transgene is over-expressed. Therefore, an understanding of biochemical mechanism that triggers the formation of recombinant protein as inclusion bodies is important before the problem can be solved. To study the biochemical changes following an over-expression of a transgene in E. coli at protein level, differential periplasmic proteome was analyzed by using a two-dimensional gel electrophoresis technique. The recombinant E. coli RG 2(DE3) carrying the plasmid pET-26b that encodes a human interferon-α2b was used as a model organism. Crude protein extracts were prepared from the periplasmic space of the E. coli cells by using an osmotic shock method. The protein samples were then separated on a 2D gel. High resolution of protein spots were successfully obtained from the protein samples after some optimizations were done on the rehydration buffer components. Optimization of CHAPS, ampholyte and DTT concentration and isoelectric focusing procedure had most effects on 2D result. Based on the software analysis of the protein spots obtained, some potential unique, up- and down-regulated protein spots were observed. Most of the up and down regulated identified proteins were shown to be involved in ABC-transporter protein family such as phosphate ABC transporter, glutathione ABC transporter and oligopeptide ABC transporter. Knowing the types of protein family responded to the transgene over-expression may provide an important clue to what triggers E.coli to produce inclusion bodies.